Risk management - Bell, David E. (Course Technology, 1995)
The book covers the following broad topics: What risk is and why businesses and individuals tend to be averse to it; The alternatives that are available for managing risk and how to use them; The extent to which unaided intuition is adequate for managing risks; Whether and when quantitative methods are useful for managers facing risky decisions.